Virginia Woolf and her doctors - Trombley, Stephen (1980)
It is generally believed that Virginia Woolf was mad. However, none of the commentators who have made this assertion have presented a clear definition of what they mean by 'madness' or 'insanity'. By reconstructing Virginia Woolf's own point of view from her autobiographical and fictional writings, it is possible to make sense of the various breakdowns and crises which marked her life, and which are reflected in her work. One theme which runs through all her work is a concern with the problem of embodiment. By turning our attention to what Virginia Woolf had to say on this subject, we can gain a deeper insight into her situation.